An investigation into the simultaneous use of a resonator as an energy harvester and a vibration absorber - Brennan, M. J. [UNESP]; Tang, B.; Pechoto Melo, G. [UNESP]; Lopes, V. [UNESP] (Elsevier B.V., 2014)
A mass-spring-damper system is at the core of both a vibration absorber and a harvester of energy from ambient vibrations. If such a device is attached to a structure that has a high impedance, then it will have very little effect on the vibrations of the structure, but it can be used to convert mechanical vibrations into electrical energy (act as an energy harvester). However, if the same device is attached to a structure that has a relatively low impedance, then the device may attenuate the vibrations as it may act as both a vibration absorber and an energy harvester simultaneously. In this paper such a device is discussed. Two situations are considered; the first is when the structure is excited with broadband random excitation and the second is when the structure is excited by a single frequency. The optimum parameters of the device for both energy harvesting and vibration attenuation are discussed for these two cases. For random excitation it is found that if the device is optimized for vibration suppression, then this is also adequate for maximizing the energy absorbed (harvested), and thus a single device can effectively suppress vibration and harvest energy at the same time. For single frequency excitation this is found not to be the case. To maximize the energy harvested, the natural frequency of the system (host structure and absorber) has to coincide with the forcing frequency, but to minimize vibration of the host structure, the natural frequency of the absorber has to coincide with the forcing frequency. In this case, therefore, a single resonator cannot effectively suppress vibration and harvest energy at the same time. (C) 2013 Elsevier Ltd. All rights reserved.